Characterization of Human Cyclin-Dependent Kinase 12 (CDK12) and CDK13 Complexes in C-Terminal Domain Phosphorylation, Gene Transcription, and RNA Processing - Liang, Kaiwei (Mol Cell Biol, 2015)
Cyclin-dependent kinase 9 (CDK9) and CDK12 have each been demonstrated to phosphorylate the RNA polymerase II C-terminal domain (CTD) at serine 2 of the heptad repeat, both in vitro and in vivo. CDK9, as part of P-TEFb and the super elongation complex (SEC), is by far the best characterized of CDK9, CDK12, and CDK13. We employed both in vitro and in vivo assays to further investigate the molecular properties of CDK12 and its paralog CDK13. We isolated Flag-tagged CDK12 and CDK13 and found that they associate with numerous RNA processing factors. Although knockdown of CDK12, CDK13, or their cyclin partner CCNK did not affect the bulk CTD phosphorylation levels in HCT116 cells, transcriptome sequencing (RNA-seq) analysis revealed that CDK12 and CDK13 losses in HCT116 cells preferentially affect expression of DNA damage response and snoRNA genes, respectively. CDK12 and CDK13 depletion also leads to a loss of expression of RNA processing factors and to defects in RNA processing. These findings suggest that in addition to implementing CTD phosphorylation, CDK12 and CDK13 may affect RNA processing through direct physical interactions with RNA processing factors and by regulating their expression.